2018
DOI: 10.18203/2349-2902.isj20185479
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing fasciitis: a tertiary centre based study

Abstract: Background: Necrotizing fasciitis is a limb or life-threatening, invasive soft-tissue infection, although known since ancient times was first described in 1871. The purpose of the present study is to analyze the clinical presentation, bacterial flora, predisposing and co-morbid conditions, surgical and resuscitative treatment and outcome of this soft tissue infection.Methods: This is a prospective, cross-sectional, clinical study which was conducted from May 2016 until April 2018. This study included 60 consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 5 publications
2
9
2
Order By: Relevance
“…In the present study, the most common site of NF infection was extremities followed by scrotum and perineum which was in accordance with a study by Singh et al The study reported most common anatomical sites with NF was lower extremities, followed by the upper extremity, and perineum (18). A prospective, cross sectional study also showed lower extremity, followed by upper extremity, and other sites such as perineum, chest, buttocks as the most common anatomical sites infected (5).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, the most common site of NF infection was extremities followed by scrotum and perineum which was in accordance with a study by Singh et al The study reported most common anatomical sites with NF was lower extremities, followed by the upper extremity, and perineum (18). A prospective, cross sectional study also showed lower extremity, followed by upper extremity, and other sites such as perineum, chest, buttocks as the most common anatomical sites infected (5).…”
Section: Discussionsupporting
confidence: 91%
“…The most pre-disposing factors observed from this study group were age, DM, and hypertension, which was in par with other reported studies (5,(18)(19)(20). In patients with DM, a delay in diagnosis of NF was apparent, especially in early stages.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The other studies, such as Divakara et al, stated that the mortality rate in their study was 12% 7 . Ekka et al found a higher mortality rate 4 . They observed 25% of mortality rate.…”
Section: Discussionmentioning
confidence: 93%